The essence and purpose of inventory accounting element (Journal of Economic Research & Business Administration, 2016)
To ensure the reliability of accounting data and financial statements, inventory of assets and liabilities, is one of the most important procedures in accounting. Physical inventory be conducted at least once a year. Number, date of event, list of assets and financial liabilities are determined by management. To ensure the completeness and accuracy of application inventory data during the inventory, and created a permanent working Commission. The actual availability of property in the inventory is determined by the Commission by means of counting, weighing, measurement, with further entering in the inventory, or acts. The inventory shall be signed by all members of the Commission and materially responsible persons. In the period between the scheduled physical inventory counts can be performed sample inventory. On the property inventory, which identified deviations from accounting data are compiled collation statements. The results of the inventory are reflected in the documents.
Keywords: The inventory of assets and liabilities; inventory Commission; the collation report; the financially responsible person.